2003
DOI: 10.1038/nature02099
|View full text |Cite|
|
Sign up to set email alerts
|

An NS3 protease inhibitor with antiviral effects in humans infected with hepatitis C virus

Abstract: Hepatitis C virus (HCV) infection is a serious cause of chronic liver disease worldwide with more than 170 million infected individuals at risk of developing significant morbidity and mortality. Current interferon-based therapies are suboptimal especially in patients infected with HCV genotype 1, and they are poorly tolerated, highlighting the unmet medical need for new therapeutics. The HCV-encoded NS3 protease is essential for viral replication and has long been considered an attractive target for therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
528
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 870 publications
(550 citation statements)
references
References 23 publications
12
528
0
5
Order By: Relevance
“…Plasma HCV RNA levels were measured using the Roche COBAS TaqMan HCV/HPS assay (Roche, Pleasanton, CA), at a central laboratory, at the time of screening and during the treatment period at days 1 and 4 and weeks 1,2,4,8,10,12,16,20,24,28,36, and 48. The LLOQ was 25 IU/mL, and the LLOD was 17 IU/mL.…”
Section: Efficacy Assessmentsmentioning
confidence: 99%
“…Plasma HCV RNA levels were measured using the Roche COBAS TaqMan HCV/HPS assay (Roche, Pleasanton, CA), at a central laboratory, at the time of screening and during the treatment period at days 1 and 4 and weeks 1,2,4,8,10,12,16,20,24,28,36, and 48. The LLOQ was 25 IU/mL, and the LLOD was 17 IU/mL.…”
Section: Efficacy Assessmentsmentioning
confidence: 99%
“…6,7 Several NS3/4 protease protease inhibitors (PIs) have been developed to block this step of the viral life cycle and have been proved, in some cases, to significantly decrease the plasma viral load of infected individuals. [8][9][10][11] Since the first description of HCV, numerous studies have described the HCV variability found in infected individuals. 12,13 The observed HCV heterogeneity, like other RNA viruses, originates from the high rate of incorrect nucleotide substitutions during viral RNA replication (10 Ϫ4 -10 Ϫ5 mutations per nucleotide and per replication cycle) 14 and rapid viral turnover (producing on average 10 12 virions per day in infected individuals).…”
mentioning
confidence: 99%
“…Several new HCV protease and polymerase inhibitors are under investigation in clinical studies and may become approved in the near future. [46][47][48][49] Kinetic analyses of monotherapy or combination therapy with new drugs that are designed to specifically inhibit viral enzymes with or without interferon can be used to compare efficacy of these new treatments with that of existing interferon-based treatments. A kinetic analysis of the serine protease inhibitor BILN 2061 demonstrated that the effectiveness in blocking viral production was dose-dependent and high compared with interferon-␣.…”
mentioning
confidence: 99%